Dietary glycerol for quail: Association between productive performance and COX III mRNA expression - Silva, S. C.C.; Gasparino, E.; Batista, E.; Tanamati, F. [UNESP]; Vesco, A. P.D.; Lala, B.; de Oliveira, D. P. [UNESP] (Genetics and Molecular Research, 2016)
This study was carry out to evaluate mRNA expression of mitochondrial cytochrome c oxidase III in the Pectoralis superficialis muscle of 28-day-old quails fed diets containing 0, 8, and 12% glycerol. Total RNA was extracted (N = 10) and cDNA was amplified using specifics primers for qRT-PCR. Feed efficiency and feed intake were evaluated. COX III mRNA expression in breast muscle was higher in the group fed with 12% glycerol (0.863 AU); no differences were observed in the expression of this gene between the muscle of animals fed diets without glycerol (0.357 AU) and 8% glycerol (0.415 AU). Quails that showed greater COX III mRNA expression also showed the lowest feed efficiency. These results show that there is a difference in COX III mRNA expression in breast muscle of 28-day-old quail fed diets different concentrations of glycerol.
Keywords: Electron transport chain; Energy metabolism; Gene expression; Oxidative phosphorylation